2010
DOI: 10.3201/eid1605.091293
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilumfrom Rodents and Sheep, China

Abstract: Three strains were isolated and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…phagocytophilum has been identified in rodents, sheep, goats, dogs, ticks, and human patients in northern China (24,27,28). A large-scale investigation of ticks (n ϭ 2,429) showed that the prevalence of A. phagocytophilum was between 1.1 and 6.0% at different sites near the China-Russia border (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phagocytophilum has been identified in rodents, sheep, goats, dogs, ticks, and human patients in northern China (24,27,28). A large-scale investigation of ticks (n ϭ 2,429) showed that the prevalence of A. phagocytophilum was between 1.1 and 6.0% at different sites near the China-Russia border (10).…”
Section: Discussionmentioning
confidence: 99%
“…marginale and A. ovis are the main ruminants pathogens found in northern China (2,15), and few studies have been carried out in central and southern China. A. phagocytophilum infections have been detected not only in ticks, rodents, and ruminants but also in the blood of human patients (4,27). Domestic ruminants infected with A. bovis have mainly been reported in African countries, but the pathogen has also been found in Japan and Korea in recent years (12,17,20).…”
mentioning
confidence: 99%
“…Although several human, ruminant, and equine strains are cultivated in ISE6 and/or IDE8 or other tick cell lines (80,147,159,234), so far, only human isolates have been directly cultured by using HL-60 cells, a human promyelocytic leukemia cell line. Recently, new strains of A. phagocytophilum from Chinese sheep and wild rodents were cultured in HL-60 cells after initial passage in BALB/c mice (246). The bacterial factors that determine virulence, host mammal species specificity, and cultivability are not known.…”
Section: Morphologymentioning
confidence: 99%
“…2). However, these sequences branched out from those of A. phagocytophilum that were detected in a patient from the United States (AF093789), a horse from Sweden (AY527214), Ixodes ovatus from Japan (AY969012), and I. persulcatus from Russia (HM366590), as well as related sequences detected in Dermacentor silvarum (DQ449948), A. agrarius (DQ342324, GQ412337), Tscherskia triton (GQ412339), and a sheep (GQ412338) from Jilin province in northeastern China (5,14). A. phagocytophilum-related sequences detected in wild rodents from Taiwan were distinct from those detected in cattle from Yonaguni Island (EU368727, EU368728), deer (AB196720) and boars in Japan, and goats (JN558811) in China (6,13,21,22).…”
mentioning
confidence: 99%